2013
DOI: 10.1098/rsta.2011.0585
|View full text |Cite
|
Sign up to set email alerts
|

Accretion disc origin of the Earth's water

Abstract: Earth's water is conventionally believed to be delivered by comets or wet asteroids after the Earth formed. However, their elemental and isotopic properties are inconsistent with those of the Earth. It was thus proposed that water was introduced by adsorption onto grains in the accretion disc prior to planetary growth, with bonding energies so high as to be stable under high-temperature conditions. Here, we show both by laboratory experiments and numerical simulations that water adsorbs dissociatively on the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
12
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 29 publications
6
12
1
Order By: Relevance
“…These results are consistent with the experimental investigation of water adsorption on olivine surfaces (Vattuone et al. ), where it was shown that even at partial pressures as low as 10 −8 bars, a hydrated olivine surface was stable at temperatures at least up to 900 K.…”
Section: Results and Discussion Of Reaction Pathwayssupporting
confidence: 92%
See 2 more Smart Citations
“…These results are consistent with the experimental investigation of water adsorption on olivine surfaces (Vattuone et al. ), where it was shown that even at partial pressures as low as 10 −8 bars, a hydrated olivine surface was stable at temperatures at least up to 900 K.…”
Section: Results and Discussion Of Reaction Pathwayssupporting
confidence: 92%
“…) as well as experimental investigations (Vattuone et al. ) that have considered this possibility have shown that water molecules could dissociate and adsorb strongly on to mineral surfaces and the resulting hydroxylated surfaces remain stable at temperatures at least up to 1200 °C at the nebular pressures. Further, temperature programmed desorption experiments demonstrated that even at low partial pressures (10 −8 bars), the olivine surface could be hydroxylated (via water dissociation) and the surface retained its water content even at high temperatures (~500–900 K) (Vattuone et al.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The construction and size of the supercell of different adsorbents is discussed in the respective sections below. We note that a similar computational methodology was used to successfully characterize the adsorption of water molecules onto mineral surfaces and thereby provide new knowledge on the accretion-disk origin of planetary water (Asaduzzaman et al, 2012aAsaduzzaman and Muralidharan, 2012;de Leeuw et al, 2010;Muralidharan et al, 2008;Prigiobbe et al, 2013;Stimpfl et al, 2006;Vattuone et al, 2013). Further, to the best of our knowledge, this is the first study which deals with quantification of organics that can be delivered to the early Earth via adsorption.…”
Section: Methodsmentioning
confidence: 89%
“…3,4 However, recent computational and experimental studies have repeatedly demonstrated that gas adsorption onto mineral dust grains in the solar nebula could also be a source of volatiles. 58 This is supported by new D/H isotopic data from a potential primordial reservoir retained in terrestrial lavas, which indicate a nebula origin of water delivered via adsorption to dust grains. 9 In all of these mechanisms, at least part of the water delivered was most likely adhered to the mineral matrix of the delivering body, whether comets, asteroids, or interplanetary dust particles.…”
Section: Introductionmentioning
confidence: 75%